Analysis of meander evolution studies on effect from land use and climate change at the upstream reach of the Pahang River, Malaysia - Kamarudin, Mohd Khairul Amri; Toriman, Mohd Ekhwan; Rosli, Mohd Hafiz; Juahir, Hafizan; Abdul Aziz, Nor Azlina; Azid, Azman; Mohamed Zainuddin, Syahrir Farihan; Sulaiman, Wan Nor Azmin (Springer Verlag, 2015)
Hydrogeomorphologically, the study of river meandering provides information on the tendency of rivers to reach and form a state of equilibrium. The process of meander changes is important in order to identify the environment-related causes that occur naturally or vice versa. Sedimentation, erosion, flood, and water quality problems usually are being specifically studied, but in a broad view, changes in the platform of the river affect all the problems that occur. This article discusses the effects of the meanders evolution changes from land use and climate change in the upstream of Sungai Pahang in over 61 years from 1932 to 1993. Based on Geographical Information System (GIS), the topographic maps, scaled to 1:50,000 in geo-reference, were overlaid and digitalized. The main alignments of the upstream reach from those years were superimposed, and the changes were identified based on sinuosity index. In this task, the study areas were divided into two major plots for river plan classification. The results indicated that the average of alignment on the sinuosity index is 1.24 to 1.48 in plot A, while in plot B, the results are not stable. Based on historical results, a very significant change of meander was identified in the subplot Ua3 in plot A, where 21.2 % segments were recorded with high changes. This could be associated with significant exploration at hilly areas in the Cameron Highlands. Large-scale changes in land use pattern are coupled with global climate change where total rainfall recorded was at 2,760 mm in plot A on the year 1993. While for the plot B segment, the percentage of meander changes is 41.5 % versus plot A which is 86.7 %. This is due to the fact that plot B is the forest reserve and national park, areas with natural environment, possessing lithosols characteristic soils in the upper plot B area, and the trend of land use change (forested areas) is substantially lower than in plot A, with a 10 % difference. The aim of this study is to understand the impact of the land use changes due to climatic conditions on the meander evolution changes at the upstream reach of the Pahang River and suggest a number of solutions to mitigate or adaptation strategies to cope with those changes in the future.